Methods to Overcome the Limits of Management Theory (Economics and region, 2021)
Scientific and technological advancements, as well as the rapid development of information technology, are bound to have an impact on business concepts. The changed socio-economic situation has led to the emergence of new and exacerbation of existing challenges and problems in management. Crisis conditions require appropriate change programs affecting all areas of the enterprise. At the same time, the difficulties of implementing changes in enterprises are determined not even by the number of actions and costs to achieve the goal, but by how much it is necessary to change each leader and each person in the organization.A well-chosen team of specialists is crucial to the success of any business. Businesses are becoming increasingly reliant on the people who work for them. With the rapid acceleration of scientific and technological advancement, as well as the implementation of a strategy for the transition to a digital economy, a correct and modern approach to human potential management is becoming increasingly important. At the micro level, the well-coordinated activity of each firm’s team assists the overall organization in reaching a qualitatively new level and achieving the established goals while taking into account the existing challenges.The article shows the process of forming the boundaries of a manager's thinking and their influence on decision-making. The urgency of changing management stereotypes to meet new economic challenges has been substantiated. An algorithm for analyzing and improving the manager's personal work is proposed. The main patterns of thinking, the reasons for their occurrence and ways to overcome them are considered. The review of previous work on this subject will enable us to analyze current human resource management issues and establish the most effective methodology for solving difficulties in the area of developing and optimizing human capital management strategies.
Keywords: delegation of authority; management theory; constructive cooperation; team